2017
DOI: 10.1111/eos.12366
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontically induced osteocyte apoptosis under different force magnitudes in rats: an immunohistochemical study

Abstract: We investigated the effect of different force magnitudes on osteocyte apoptosis in a model of orthodontic tooth movement. Forty-nine male Sprague Dawley rats (7-9 wk of age) were divided into light- and heavy-force groups (n = 21 each group) and a control group (n = 7). A coil spring delivered pressure (either 10-15 g or 20-25 g) to the left maxillary first molar. The rats were sacrificed 1, 3, or 5 d after placement of the appliance. Sections of the maxillary first molars were immunostained for caspase-3. Upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Although the distribution of apoptotic caspas3 + cells in the tension areas was unrelated to the force intensity. [30] According to the clinical study conducted by Leon et al, 8 months after the application of orthodontic force, the content of BCL2 protein in dental human pulp decreased in a time-dependent manner while the expression level of caspase9 increased. They reported that the orthodontic treatments reduced BCL2 expression time-dependently, resulting in increased cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Although the distribution of apoptotic caspas3 + cells in the tension areas was unrelated to the force intensity. [30] According to the clinical study conducted by Leon et al, 8 months after the application of orthodontic force, the content of BCL2 protein in dental human pulp decreased in a time-dependent manner while the expression level of caspase9 increased. They reported that the orthodontic treatments reduced BCL2 expression time-dependently, resulting in increased cell death.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that orthodontic forces cause a significant increase in osteocyte apoptosis and that its peak (24–48 h of OTM) precedes the appearance of osteoclasts [ 14 , 23 ]. Osteocytes are deeply embedded in mineralized matrix and are not accessible by scavengers that phagocytose cells undergoing apoptosis and prevent inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Ten of the extracted supernumerary teeth were stored in saline until processed for histopathological and immunohistochemical analysis. Sections from formalin-fixed paraffin-embedded (FFPE) blocks were prepared according to Kassem et al [ 16 ]; one section was stained with hematoxylin and eosin, and four unstained slides were prepared for immunohistochemistry (IHC). For IHC, FFPE sections were deparaffinized in xylene and rehydrated in graded ethanol concentrations.…”
Section: Methodsmentioning
confidence: 99%